Nudging in Complex Environments - Alexander K. Koch; Dan Monster; Julia Nafziger (Institute of Labor Economics (IZA), 2023)
To study the effects of reminder nudges in complex environments, we apply a novel experimental approach based on a computer game in which decision makers have to pay attention to and perform multiple actions within a short period of time. The set-up allows us, first, to test the effect of reminders both on reminded and non-reminded actions and thus to observe whether reminders have (positive or negative) spillovers. Second, we investigate spillovers between multiple nudges by testing the effect of scaling up the number of reminded actions. Third, we study intertemporal spillovers by investigating whether the effects of having been exposed to reminders persist after reminders are withdrawn. We observe that reminders have positive effects in the short run – multiple reminders more so than single reminders: while reminders lead to crowding-out of non-reminded actions, the positive effect on the reminded actions dominates. Yet, after withdrawal of the reminders, the negative spillover effect persists, while the positive effect partially fades out so that, overall, reminders have no effect.
Keywords: C9; D91; 330; nudging; spillover effects; attention; reminders; persistence; game-based experiments